Volume extreme ultraviolet holographic imaging with numerical optical sectioning - Rocca, J. J., author; Menoni, C. S., author; Bartels, R. A., author; Marconi, Mario Carlo, author; Wachulak, P. W., author; Optical Society of America, publisher (Colorado State University. Libraries, 2007)
Three dimensional images were obtained using a single high numerical aperture hologram recorded in a high resolution photoresist with a table top λ = 46.9 nm laser. Gabor holograms were numerically reconstructed over a range of image planes by sweeping the propagation distance in the numerical reconstruction algorithm, allowing numerical optical sectioning. A robust three dimension image of a test object was obtained with numerical optical sectioning, providing a longitudinal resolution of approximately 2 μm and a lateral resolution of 164 nm.